2021
DOI: 10.1111/dth.15093
|View full text |Cite
|
Sign up to set email alerts
|

COVID ‐19 vaccine‐induced urticarial vasculitis

Abstract: Urticarial vasculitis (UV) is characterized by persistent urticarial rashes that last for more than 24 h and heals with hyperpigmentation. It can be idiopathic or due to drugs, infections, malignancy, autoimmune or autoinflammatory diseases. 1 Rarely, vaccines have been implicated in the causation of UV. 2,3 A 27-year-old man developed multiple itchy reddish, elevated lesions following one after the second dose of COVID-19 vaccine (whole virion inactivated coronavirus vaccine). It was associated with fever and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…Three cases were published in association with COVID‐19 vaccination. Two after the first dose of Moderna vaccine 34,38,48 …”
Section: Resultsmentioning
confidence: 99%
“…Three cases were published in association with COVID‐19 vaccination. Two after the first dose of Moderna vaccine 34,38,48 …”
Section: Resultsmentioning
confidence: 99%
“…The first case of vaccine‐induced urticarial vasculitis, which was reported by Siddhartha Dash after the second dose of COVID‐19 vaccination for a patient who was not infected previously with COVID‐19 virus, suggested that the marked inflammatory response was the leading cause for vascular inflammation after the second dose. 7 In our case, it can be suggested that antigen had presented after COVID‐19 infection and the hypersensitivity inflammatory aroused after the first dose of vaccine, which mean that this patient has developed a considerable inflammatory response leading to this presentation. More studies are needed to know the exact type of the antibodies leading for this reaction.…”
Section: Figurementioning
confidence: 65%
“…Reportedly, vasculitis accounted for 2.9 and 0.7% of the cutaneous side effects in patients receiving the first doses of Pfizer-BioNTech and Moderna (mRNA-1273) vaccines, respectively [ 11 ]. The disease was limited to cutaneous vasculitis in most patients [ 5 , 6 , 8 ]; however, organ involvement was reported in some cases. Shakoor et al.…”
Section: Discussionmentioning
confidence: 99%